2013
DOI: 10.1037/a0032622
|View full text |Cite
|
Sign up to set email alerts
|

Drug trafficking and immigration: Impact on the borderlands culture of South Texas.

Abstract: Mexico borderlands milieu has been described as interdependent. Recent changes resulting from drug trafficking, immigration, and border security have been viewed as a threat to that cooperative milieu. This 10-year intergenerational longitudinal study in 5 nonmetropolitan U.S.-Mexico border communities in South Texas investigated the relation between (a) drug trafficking and related violence, recent immigration from Mexico, and increased border security measures, and (b) frequency of cross-border travel among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The borderlands have been the focus of substantial recent media attention due to elevated drug trafficking and drug‐related violence, and remain an area of high policy and legal tension (Ramirez et al., ). Until recently, however, large‐scale epidemiological studies focusing on alcohol and drugs have been lacking.…”
mentioning
confidence: 99%
“…The borderlands have been the focus of substantial recent media attention due to elevated drug trafficking and drug‐related violence, and remain an area of high policy and legal tension (Ramirez et al., ). Until recently, however, large‐scale epidemiological studies focusing on alcohol and drugs have been lacking.…”
mentioning
confidence: 99%
“…Our findings indicate that in the drug wars era, native borderlander Mexican Americans are associating new immigrants from Mexico with drug trafficking and related crimes (Ramirez, Argueta, and Grasso 2013). They also strongly believe that the newcomers are defrauding government assistance programs (Miller, Polinard, and Wrinkle 1984; Polinard, Wrinkle, and de la Garza 1984; De la Garza et al 1991; Binder, Polinard, and Wrinkle 1997).…”
Section: Analyses and Conclusionmentioning
confidence: 80%
“…More recently, Schaan (2009) has noted that drug trafficking and violence in Mexico are having a spill-over effect that is changing the milieu of US borderlands communities. Ramirez, Argueta, and Grasso (2013) found that US–Mexico borderland community residents perceived that drug violence on the Mexican side of the border was spilling over into the US. Furthermore, this belief was related to their distrust of recent immigrants from Mexico, fearing that many of them might be associated with the cartels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation